A Prospective, Crossover, Randomized, Double-Blind Clinical Study Comparing the Effectiveness and Ocular Comfort of 0.1% Hyaluronic Acid and 0.3% Hyaluronic Acid in Patients With Dry Eye Disease - Kim SJ; Yoo WS; Kwon LH; Kim RB; Yoon HJ; Yoon KC (Clinical Ophthalmology)
Seong-Jae Kim,1,* Woong-Sun Yoo,1,* Lee-Ha Kwon,1 Rock Bum Kim,2,3 Hyeon-Jeong Yoon,4 Kyung Chul Yoon4 1Department of Ophthalmology, Institute of Medical Science, Gyeongsang National University Hospital, Gyeongsang National University College of Medicine, Jinju, South Korea; 2Regional Cardiocerebrovascular Disease Center, Gyeongsang National University Hospital, Jinju, South Korea; 3Department of Preventive Medicine, Institute of Medical Science, Gyeongsang National University College of Medicine, Jinju, South Korea; 4Department of Ophthalmology, Chonnam National University Medical School, Gwangju, South Korea*These authors contributed equally to this workCorrespondence: Kyung Chul Yoon, Department of Ophthalmology, Chonnam National University Medical School, #42 Jebong-ro, Dong-gu, Gwangju, 61469, South Korea, Tel +82-62-220-6753, Fax +82-62-227-1642, Email kcyoon@jnu.ac.krPurpose: Report the clinical effects and discomfort of using 0.1% hyaluronic acid (HA [Kynex 1®, Alcon, Seoul, S. Korea]) and 0.3% HA (Kynex 3®, Alcon, Seoul, S. Korea) to treat dry eye disease (DED).Methods: This study was designed as a prospective, crossover, randomized, and double-blind study. Patients aged > 19 years with DED level 2 or higher, corneal staining score > 1, and tear break-up time (TBUT) < 10s were included. Sixty patients were randomly assigned to two groups. Patients in group 1 were instilled with 0.1% HA for four weeks and then 0.3% HA for the next four weeks. Group 2 patients were instilled with the eye drops in the reverse order of group 1. Patients were evaluated using a corneal staining score, TBUT, and the Standardized Patient Evaluation of Eye Dryness (SPEED) questionnaire at baseline, four weeks, and eight weeks.Results: In both groups, 0.3% HA showed an increasing trend in TBUT, although the difference was not statistically significant. Changes in the Schirmer test were greater in group 2, but this difference was also not statistically significant. The corneal staining score improved in both groups, with no statistically significant difference. While 0.3% HA was more effective than 0.1% HA according to the absolute value, this difference was not statistically significant. There was no difference between the two groups in the SPEED questionnaire evaluation that assessed aspects of discomfort, such as blurred vision, foreign body sensation, and burning sensation.Conclusion: 0.3% HA was more effective for treating DED, although the difference was not statistically significant. In terms of discomfort, 0.3% HA showed no difference compared to 0.1% HA. Using both 0.1% HA and 0.3% HA in a tailored treatment approach can improve patient comfort and treatment outcomes.Plain Language Summary: Dry eye disease (DED) is a common condition that causes discomfort and vision problems. This study aimed to find out how well two eye drops, using 0.1% hyaluronic acid (HA [Kynex 1®, Alcon, Seoul, S. Korea]) and 0.3% HA (Kynex 3®, Alcon, Seoul, S. Korea), work in treating DED and how comfortable they are for patients to use. We included 60 adults with moderate to severe DED and divided them into two groups. One group used 0.1% HA for four weeks and then switched to 0.3% HA for another four weeks, while the other group used the drops in the opposite order. We evaluated their symptoms and signs at the beginning, after four weeks, and after eight weeks using ophthalmologic examinations and a questionnaire. Both eye drops helped improve the symptoms of DED, with 0.3% HA being slightly more effective overall, although the difference was not significant. Both eye drops were similarly comfortable for the patients. The study shows that both 0.1% HA and 0.3% HA are effective treatments for DED. While 0.3% HA might have a slight edge in effectiveness, both drops can be used to improve patient comfort and outcomes. Using these eye drops in a personalized treatment plan can help people with DED manage their symptoms better and lead more comfortable lives.Keywords: dry eye disease, 0.1% hyaluronic acid, 0.3% hyaluronic acid